Использование технологии критического мышления на уроках биологии - Вартаньян, Г.В. (My University, 2013)
Currently, relevant in the education system are educational technology, aimed at the identification and development of creative abilities of students. Therefore, the modern teacher must take into account and provide an environment in the classroom, which could contribute to the realization of its creative potential. The student must be able not only to study in the framework of the ideology of "repeating the teacher said," but also to think, to find the necessary solutions of known issues, analyze, work with different sources of information. It is, therefore, the organization of the educational process, which includes the technology of "critical thinking" is a tool that allows you to take a fresh look at the educational process. Lessons from the use of "critical thinking" are aimed at encouraging students to mental activity and promotes their activation to find the answer.